2008
DOI: 10.1517/14712590802510629
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interferon beta-1b on size of short-lived enhancing lesions in patients with multiple sclerosis

Abstract: Background Contrast enhancing lesions (CELs) in MRI represent inflammatory events in multiple sclerosis (MS). IFN-β-1b decreases the formation of CELs. However, the ability of IFN-β-1b to reduce the size of CELs arising during therapy has not been extensively investigated. Methods Thirty patients with relapsing-remitting (RR) MS were followed for a 3-month pre-therapy phase then for a 6-month therapy phase during which treatment with IFN-β-1b at a dosage of 250 μg subcutaneously injected every other day was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The AUC was derived from individual posterior Bayes estimates of CL using a sequential analysis approach . The monthly cumulative AUC was selected to represent exposure because interferon reduced acute inflammation as early as within a month of treatment initiation, and acute inflammation was associated with relapses . Therefore, reduction of ARR is considered a cumulative effect of peginterferon beta‐1a, and the exposure was represented by AUC.…”
Section: Methodsmentioning
confidence: 99%
“…The AUC was derived from individual posterior Bayes estimates of CL using a sequential analysis approach . The monthly cumulative AUC was selected to represent exposure because interferon reduced acute inflammation as early as within a month of treatment initiation, and acute inflammation was associated with relapses . Therefore, reduction of ARR is considered a cumulative effect of peginterferon beta‐1a, and the exposure was represented by AUC.…”
Section: Methodsmentioning
confidence: 99%
“…Because the conversion of CELs into black holes is an indirect sign of more aggressive pathology, it was concluded that IFNβ‐1b was not able to affect the severity of CELs once these were formed. In a larger cohort of 30 patients with RRMS treated with IFNβ‐1b at the same dosage and regimen, it was found that although the count of CELs was dramatically reduced during treatment, the average size of each CEL was not affected . The results of the current analysis provide an additional demonstration that IFNβ‐1b, on a population level, may affect the count of CELs, but once a CEL is formed the medication is not effective in promoting lesion resolution.…”
Section: Discussionmentioning
confidence: 63%
“…A relatively large study performed in the NINDS group during a short-term (six-month) time window, has shown that the effect of IFNβ-1b in reducing the likelihood of CEL formation is not paralleled by its ability to reduce the size of CELs once formed. 47 IFNβ-1b reduced the number of CELs by 76.4 % over 18 months of therapy. This decrease however, was statistically greater for small lesions enhancing only once during therapy (82.3 %) than for larger ones enhancing multiple times (57.4 %).…”
Section: Interferon Beta-1b Effect On Contrast-enhancing Lesion Qualitymentioning
confidence: 93%